iRhom2 inhibits bile duct obstruction-induced liver fibrosis - Sundaram, Balamurugan; Pellegrino, Rossella; Longerich, Thomas (Science signaling, 2019)
iRhom2 protects against liver fibrosis - Injury or chronic inflammation in the liver leads to the activation of hepatic stellate cells, which transdifferentiate into matrix-secreting myofibroblasts that promote fibrosis. Sundaram et al. found that mice lacking the rhomboid family pseudoprotease iRhom2, which is required for the proper trafficking and activation of the metalloprotease ADAM17 (see the Focus by Badenes and Adrain), showed increased stellate cell activation and susceptibility to liver fibrosis induced by bile duct ligation (BDL). iRhom2-dependent activation of ADAM17 promoted shedding of tumor necrosis factor receptors (TNFRs) from hepatic stellate cells. Treating iRhom2-deficient mice with the TNF-α inhibitor etanercept reduced BDL-induced stellate cell activation and liver fibrosis. Data from patients with liver cirrhosis were consistent with these observations, suggesting a protective role for iRhom2 in human liver disease. - Chronic liver disease can induce prolonged activation of hepatic stellate cells, which may result in liver fibrosis. Inactive rhomboid protein 2 (iRhom2) is required for the maturation of A disintegrin and metalloprotease 17 (ADAM17, also called TACE), which is responsible for the cleavage of membrane-bound tumor necrosis factor-α (TNF-α) and its receptors (TNFRs). Here, using the murine bile duct ligation (BDL) model, we showed that the abundance of iRhom2 and activation of ADAM17 increased during liver fibrosis. Consistent with this, concentrations of ADAM17 substrates were increased in plasma samples from mice after BDL and in patients suffering from liver cirrhosis. We observed increased liver fibrosis, accelerated disease progression, and an increase in activated stellate cells after BDL in mice lacking iRhom2 (Rhbdf2−/−) compared to that in controls. In vitro primary mouse hepatic stellate cells exhibited iRhom2-dependent shedding of the ADAM17 substrates TNFR1 and TNFR2. In vivo TNFR shedding after BDL also depended on iRhom2. Treatment of Rhbdf2−/− mice with the TNF-α inhibitor etanercept reduced the presence of activated stellate cells and alleviated liver fibrosis after BDL. Together, these data suggest that iRhom2-mediated inhibition of TNFR signaling protects against liver fibrosis. - iRhom2 reduces hepatic stellate cell activation and liver fibrosis after bile duct ligation. - iRhom2 reduces hepatic stellate cell activation and liver fibrosis after bile duct ligation.
Gesehen am 11.12.2019